Content Analysis Of Writing Tasks In The English Textbook “When English Rings A Bell” For Eighth-Grade Students Of Junior High School Based Paul Nation Theory - Intan Novita Sari; Dwi Andriani; Arief Hadziq Fikri (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research was aimed to find out whether the writing task in the “English Rings A Bell” textbook based on the criteria of writing task as suggested by Paul Nation theory. The method of this research was descriptive qualitative. To analysed the data, the researcher used the qualitative content analysis method. The researcher found 25 kinds of writing tasks divided into 1 task from experience task from the types draw and write with percentage (7,40%). 1 task from share task, 4 tasks from group composition with percentage (14,81%). 7 tasks from the guided task, 3 tasks (11,11%) from types look and write, 2 tasks (7,40%) from types complete the sentence and 1 task (3,70%) from types change the sentence. The last 13 tasks from the independent task with a percentage of 48,14%. Based on the percentage whether the tasks provided in the English textbook are based on the criteria of writing tasks as suggested by Paul Nation proposed by Arikunto are 22,22 %. The dominant writing task way found in this English textbook was Independent Task (48,14%).